Preparation method of slag-based geopolymer cementing material and application of slag-based geopolymer cementing material in building materials
By using slag and fly ash as raw materials and using water glass as exciters, the composition of raw materials is simplified and the mechanical properties are improved, the problems of complex and insufficient raw materials in the existing technology are solved, and efficient replacement of gelled materials is achieved Cement meets the stability and strength requirements of the highway base.
Patent Information
- Application Number
- CN202411308174.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-27
AI Technical Summary
The raw material composition of the existing slag base polymer cementitious materials is complex and has insufficient mechanical properties, making it difficult to effectively replace cement and meet the stability and strength requirements of the highway base.
Using slag and fly ash as precursors and water glass as alkali exciters, a slag base polymer gelling material is prepared by adjusting the mass ratio of slag and fly ash, the dosage and modulus of water glass, and simplifying the The raw material composition is improved and the mechanical properties of the material are improved.
It has achieved easy access to raw materials and simple preparation methods. The cementitious material can partially or completely replace cement, which significantly improves the stability and strength of the highway base and meets the requirements of pavement bases of different highway grades.
Smart Images

Figure CN119191771A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a preparation method of a slag-based polymer gelling material and an application thereof in building materials. Background Art
[0002] With the rapid and vigorous development of highway construction, the carbon dioxide produced in the process of cement production accounts for a large proportion of the total carbon dioxide emissions. In order to save energy and reduce emissions, seeking a new cementitious material to replace or reduce the use of cement is a topic worthy of in-depth discussion. In road engineering, the use of appropriate methods to treat and utilize large amounts of industrial solid waste can not only effectively reduce environmental pollution, but also reduce material costs and improve road performance. This method has become a trend of the development of the times. The comprehensive utilization of industrial waste residues will become an important direction for the development of road engineering and has broad prospects for engineering applications.
[0003] The patent with application number 202410738632.1 proposes a cementitious material for highway pavement base, its preparation method and application. The cementitious material includes modified basalt powder, slag composite powder, desulfurized gypsum, 42.5 ordinary Portland cement, and modified admixtures. Among them, the modified basalt powder is prepared using basalt, limestone, and desulfurized gypsum as raw materials. Although the cementitious material can effectively reduce the risk of cracking in the later stage of the highway base, the raw material composition is complex and difficult to obtain. The patent with application number 202210872699.5 proposes a method for preparing a roadbed early-strength cementitious material, which first pre-treats phosphogypsum and phosphate tailings, then mixes the pre-treated phosphate tailings and fly ash to prepare stewing material, then reasonably proportions the pre-treated phosphogypsum and stewing material, and finally adds alkaline calcium activator, adhesive, water reducer and water to mix evenly. The preparation method of this material is relatively complicated. The patent with application number 202110481718.7 proposes an all-solid waste cementitious material, its preparation method and application. The raw materials include 22.5% to 27.5% phosphogypsum, 22.5% to 27.5% carbide slag, and 45% to 55% slag powder. The moisture content of the all-solid waste roadbed and pavement material after solidification is 54%, and the 28d compressive strength is only 4.9MPa.
[0004] In view of this, how to provide a slag-based polymer cementitious material with a simpler raw material composition and further improved mechanical properties is a problem that needs to be solved urgently in the art. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes a method for preparing a slag-based polymer cementitious material and its application in building materials.
[0006] To achieve the above-mentioned purpose, the present invention provides a slag-based polymer cementitious material (NSF material), which uses slag and fly ash as precursors and water glass as an alkali activator, wherein the mass ratio of the slag to the fly ash is (5-7): (3-5), the amount of the water glass in the precursor is 15-25wt%, and the modulus of the water glass is 1.0-1.4.
[0007] Preferably, the mass ratio of the slag to the fly ash is 5:5, the content of the water glass in the precursor is 15wt%, and the modulus of the water glass is 1.0.
[0008] Preferably, the raw materials of the slag-based polymer cementitious material further include standard sand, naphthalene-based water reducer and water.
[0009] Preferably, the water-to-cement ratio of the slag-based polymer cementitious material is 0.4.
[0010] The present invention also proposes a method for preparing the slag-based polymer cementitious material, comprising the following steps: mixing water glass with water, adding slag, fly ash, standard sand and naphthalene-based water reducer, mixing and stirring to obtain the slag-based polymer cementitious material.
[0011] The invention also proposes the application of the slag-based polymer cementitious material in road construction materials.
[0012] Preferably, the slag-based polymer cementitious material is used for stabilizing crushed stone in the road base, and the addition amount of the slag-based polymer cementitious material is 4%-5%.
[0013] Preferably, the slag-based polymer cementitious material is used for pavement base stabilized soil or concrete, and the addition amount of the slag-based polymer cementitious material is 6-12%, and more preferably the addition amount is 10%.
[0014] The hydration principle of the slag-based polymer gelling material of the present invention is:
[0015] The hydrated sodium silicate in water glass is hydrolyzed to generate NaOH and Si(OH)4. -Under the action of , the water glass stimulated slag fly ash system is mainly generated by the hydrolysis of slag to form CSH and CSAH gels in the early stage, and the fly ash mainly reacts in the later stage to form C(N)-SAH. In the final system, amorphous CSH, C(N)-SAH, and NSAH gels are intertwined to form the strength of the system. The main component of water glass is Na2SiO3, and sodium silicate has a dual effect on the stimulation of slag fly ash: sodium silicate hydrolyzes to form sodium hydroxide, which creates a strong alkaline environment and mainly plays a role in breaking bonds in the early stage of hydration; Si(OH)4 produced by the hydrolysis of water glass helps to eliminate the supersaturation of silicon oxygen anion groups around fly ash and slag, promotes the depolymerization process of fly ash and slag, forms crystal nuclei and reduces the nuclear energy of hydration products.
[0016] Compared with the prior art, the present invention has the following advantages and technical effects:
[0017] (1) The raw materials of the slag-based polymer cementitious material of the present invention are easily available, and the preparation method is simple. The obtained cementitious material can partially or completely replace cement, and can be further used in the preparation of highway base stabilized gravel, stabilized soil and concrete.
[0018] (2) The slag-based polymer cementitious material obtained by the present invention uses slag and fly ash industrial solid waste as raw materials. The interweaving and overlapping of the gel products can more effectively fill the pores in the matrix, reduce the porosity of the matrix, and form a more compact cementitious structure, thereby improving the mechanical properties of the material. The micro-aggregate effect, ball effect, and volcanic ash effect of fly ash all play a role in increasing the strength of the system. When cement-NSF is used to stabilize gravel, as the proportion of NSF increases, the unconfined compressive strength, indirect tensile strength, and compressive rebound modulus all increase to varying degrees. The 7d unconfined compressive strength and road performance of the gravel mixture stabilized by a 4% cement-NSF cementitious material can meet the requirements of the pavement base of different highway grades.
[0019] (3) The biggest drawback of existing slag / fly ash-based oligomer gelling agent materials is that they have a fast setting time and a large shrinkage, which affects various performances when they are subsequently used in building materials. The present invention adjusts the mass ratio of slag and fly ash, the water glass output and modulus and other parameters so that the prepared gelling material can partially or even completely replace cement and is well used in the preparation of highway base stabilized gravel, stabilized soil and other scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0021] Figure 1This is a photo of the molded test block in Example 1;
[0022] Figure 2 The compressive strength of NSF cement mortar varies with the mix ratio of slag-fly ash;
[0023] Figure 3 The compressive strength of NSF cement mortar varies with the amount of activator added;
[0024] Figure 4 The results of the effect of water glass modulus on the compressive strength of NFS cement mortar;
[0025] Figure 5 The results of the influence of the content of each component of slag-fly ash on the setting time of NSF cement mortar;
[0026] Figure 6 The results of the effect of alkali activator dosage on the setting time of NSF cement mortar;
[0027] Figure 7 The results of the effect of water glass modulus on the setting time of NSF cement mortar;
[0028] Figure 8 The results of the influence of the content of each component of slag-fly ash on the shrinkage of NSF cement mortar;
[0029] Fig. 9 The results of the influence of water glass modulus on the shrinkage of NSF cement mortar;
[0030] Fig.10 This is the SEM image of NFS cement mortar (specimen I) at 14 days;
[0031] Fig.11 This is the SEM image of NFS cement mortar (specimen I) at 28 days;
[0032] Fig.12 XRD patterns of NFS cement mortar (specimen I) at 3d, 14d and 28d;
[0033] Fig.13 is the aggregate grading curve in Application Example 1;
[0034] Fig.14 The maximum dry density of cement-NSF crushed stone mixture under different NSF dosages is measured;
[0035] Fig.15 The results of the determination of the optimum moisture content of cement-NSF crushed stone mixture at different NSF dosages;
[0036] Fig.16is the unconfined compressive strength of cement-NSF crushed stone mixture at different NSF dosages when the mass proportion of cement-NSF in the cement-NSF crushed stone mixture is 4%;
[0037] Fig.17 is the unconfined compressive strength of cement-NSF crushed stone mixture at different NSF dosages when the mass proportion of cement-NSF in the cement-NSF crushed stone mixture is 5%;
[0038] Fig.18 is the indirect tensile strength of cement-NSF crushed stone mixture under different NSF dosages when the mass proportion of cement-NSF in the cement-NSF crushed stone mixture is 4%;
[0039] Fig.19 is the indirect tensile strength of cement-NSF crushed stone mixture under different NSF dosages when the mass proportion of cement-NSF in the cement-NSF crushed stone mixture is 5%;
[0040] Fig. 20 is the compressive rebound modulus of cement-NSF crushed stone mixture under different NSF dosages when the mass proportion of cement-NSF in the cement-NSF crushed stone mixture is 4%;
[0041] Fig.21 is the compressive rebound modulus of cement-NSF crushed stone mixture under different NSF dosages when the mass proportion of cement-NSF in the cement-NSF crushed stone mixture is 5%;
[0042] Fig. 22 It is the relationship curve of the cumulative water loss rate of the mixture with time under different NSF cementitious material dosage;
[0043] Fig.23 It is the relationship curve of the shrinkage strain of the mixture with time under different NSF cementitious material dosage;
[0044] Fig.24 It is the relationship curve of the cumulative shrinkage strain of the mixture with time under different NSF cementitious material dosage;
[0045] Fig.25 It is a curve diagram showing the relationship between the shrinkage coefficient of the mixture and time at different NSF cementitious material dosages;
[0046] Fig.26 This is the SEM image of the cement-NSF crushed stone mixture of Group II in Application Example 1 after 7 days;
[0047] Fig. 27 This is the SEM image of the cement-NSF crushed stone mixture 28d of Group II in Application Example 1. DETAILED DESCRIPTION
[0048] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0049] The slag used in the embodiment of the present invention is water-quenched blast furnace slag provided by a steel plant in Tangshan City, Hebei Province, which is S95 grade granulated blast furnace slag powder with a specific surface area of 400m 2 / kg, and its performance meets the requirements of "Granulated blast furnace slag powder for cement, mortar and concrete" (GB / T 18046-2017).
[0050] The fly ash used in the embodiment of the present invention comes from a power plant in Shanxi and is Grade II, and its performance meets the requirements of "Fly ash used in cement and concrete" (GB / T 1596-2017).
[0051] The alkaline activator used in the embodiment of the present invention is water glass (sodium silicate), which is liquid sodium silicate with a grade of two. The modulus of the sodium silicate used in the embodiment is 1.0-1.4, so the modulus of the water glass should be adjusted according to NaOH (produced by a chemical plant in Tianjin). Because there is also free water in the water glass solution, take the preparation of 100 mg of water glass solution with a modulus of 1.2 as an example, in which the mass fractions of SiO2 and Na2O are 26.54% and 22.82% respectively, and the mass of free water in the water glass solution is 50.64g. The mass of additional water to be added is according to the following formula: m=450×0.4-m 自由水 .
[0052] The cement used in the embodiment of the present invention is Hebei Tangshan Aota brand P·O42.5 cement.
[0053] The natural aggregate used in the embodiment of the present invention is limestone from the Zhangjiakou quarry in Hebei Province, which meets the requirements of the Technical Specifications for Highway Pavement Base Construction (JTG / TF20-2015).
[0054] The subgrade soil used in the embodiments of the present invention comes from the Qugang Expressway connecting line in Lixian County, Baoding, Hebei Province. Its main components include SiO2, Al2O3, Fe2O3, TiO2 and a small amount of crystal water, which meets the requirements of soil in the "Highway Geotechnical Test Code" (JTGE40-2007).
[0055] The naphthalene-based water reducer used in the embodiment of the present invention is a high-efficiency water reducer and can be purchased commercially.
[0056] The soil used in the present invention is the foundation soil of a high-speed connecting line in Hebei.
[0057] The technical solution of the present invention is further illustrated by the following embodiments.
[0058] Examples 1 to 9
[0059] According to Table 1, Examples 1 to 9 were set up, the water-to-binder ratio of the cementitious material was fixed at 0.4, slag and fly ash were used as precursors, the fixed mass of the precursors was 450 g, and 1% naphthalene-based water reducer was added (accounting for the mass fraction of the cementitious material powder).
[0060] Table 1 Composition of Examples 1-9
[0061]
[0062] Note: A is the mix ratio of slag-fly ash, B is the dosage of alkali activator (water glass) solution (%, the same below); C is the modulus of alkali activator (water glass) solution, and D is a fixed water-binder ratio of 0.4.
[0063] According to the mix ratio in Table 1, the slag-based oligomer cementitious material was prepared into cement mortar according to the method specified in "Test Method for Cement Mortar Strength (ISO Method)" (GB / T17671-2021), and the strength influencing factors, setting time, shrinkage performance, etc. of cement mortar at various ages were further determined. The preparation method of cement mortar specimens is as follows:
[0064] According to the above method, Table 2 (the mass of water that needs to be added to the water glass solution) is obtained. According to the ratio of the water glass activator solution and water in Table 2, mix them in a stirring pot, and then add 450g of the well-proportioned slag and fly ash mixed powder. After fixing the stirring pot, pour 1350g of standard sand into the container, and start the automatic stirring function. After 30 seconds of slow stirring, the mixer automatically adds sand and stirs quickly for 60 seconds. Then stop stirring for 90 seconds, and use a scraper to clean the blades and inner wall of the stirring pot, scrape the mortar mixture into the pot, and then stir at high speed for 60 seconds. After the stirring is completed, take out the mixture, add it into a 40mm×40mm×160mm triple steel mold twice, and use a vibrating table to vibrate it. After vibrating, use a scraper to scrape the surface of the mortar flat, and place the formed test block (see Figure 1 ) together with the test mold, put it into a standard curing box for 24 hours of curing. The curing conditions are generally 20℃±1℃, relative humidity 95%, and after curing until the shape is fixed, demoulding is carried out normally. After demoulding, the test piece is placed in a curing water tank for immersion curing.
[0065] Table 2 The mass of water to be added in each group of water glass solution
[0066]
[0067]
[0068] The performance test results of cement mortar prepared according to the proportions of slag-based polymer cementitious materials (NFS) in Examples 1 to 9 are as follows:
[0069] 1. Compressive strength test
[0070] Cement mortar specimens with a curing age of 3d, 14d and 28d were selected for compressive strength tests. The test results are shown in Table 3.
[0071] Table 3 Compressive strength test results of cement mortar specimens
[0072]
[0073] The compressive strength of NSF cement mortar varies with the slag-fly ash mix ratio. Figure 2 .Depend on Figure 2 It can be seen that when the slag content in the cementitious material is high and the fly ash content is low, the compressive strength of the specimen is relatively low. In this system, the hydration activity of slag is the highest.
[0074] The compressive strength of NSF cement mortar varies with the amount of activator added. Figure 3 .Depend on Figure 3 It can be seen that when the alkali activator dosage is 20%, the compressive strength of NSF is greater than that of 15% and 25%. The main reason is that when the alkali activator dosage is too low, the compressive strength of NSF is low. This is mainly because the NSF cementitious material system is a quantitative reaction chemical process. The alkali activator can accelerate the hydration reaction of the geopolymer. Too low alkali activator dosage will slow down the hydration reaction, and the glass phase in the slag and fly ash cannot be fully disintegrated, which limits the activation of the activity of these solid wastes and the breaking of the Ca-O bond. It cannot effectively activate the activity of the NSF material, so the strength will be relatively low. When the alkali activator dosage is too high, a passivation reaction occurs, and the water glass solution will increase the viscosity of the solution, which will weaken the fluidity of the NSF slurry, reduce the ion reaction rate in the system, affect the generation rate of CSH gel, reduce the internal density of the structure, and the excess Na2SiO3 will crystallize into Na2SiO3·9H2O during the curing process, resulting in an unstable internal structure and significantly reducing the strength of the cementitious material.
[0075] The effect of water glass modulus on the compressive strength of NFS cement mortar is shown in Figure 4 ,Depend on Figure 4 It can be seen that when the modulus of water glass decreases, adding too much NaOH causes the hydration reaction of the system to proceed rapidly, and a large amount of gel is generated in a short time to wrap the surface of slag and fly ash particles, preventing the hydration reaction of the system from proceeding; when the modulus of water glass is large, less NaOH solid is added, the pH of the solution decreases, the depolymerization degree of silicon aluminum oxides in the aluminosilicate minerals in fly ash and slag becomes smaller, and the generated Ca 2+ 、[SiO4] 4- 、[A1O4] 5-Less, which is not conducive to the formation and development of the compressive strength of the specimen.
[0076] 2. Determination of coagulation time
[0077] The results of the initial setting time and final setting time of NFS cement mortar are shown in Table 4.
[0078] Table 4 NFS cement mortar initial setting time and final setting time test results
[0079] Initial setting time / min Final setting time / min Example 1 260 460 Example 2 224 420 Example 3 253 451 Example 4 216 406 Example 5 238 426 Example 6 246 443 Example 7 184 361 Example 8 206 402 Example 9 181 357
[0080] The results of the influence of the content of each component of slag-fly ash on the setting time of NSF cement mortar are shown in Figure 5 ,Depend on Figure 5 It can be seen that when the slag content in the cementitious material is high and the fly ash content is low, the initial setting time and final setting time of NSF cement mortar are shortened accordingly. However, even if the content reaches 70%, its setting time (initial setting 181min, final setting 357min) can meet the requirements of engineering applications.
[0081] The results of the effect of alkali activator dosage on the setting time of NSF cement mortar are shown in Figure 6 ,Depend on Figure 6 It can be seen that when the amount of alkali activator in the cementitious material is high, the initial setting time and final setting time of NSF are prolonged accordingly.
[0082] The results of the effect of water glass modulus on the setting time of NSF cement mortar are shown in Figure 7 ,Depend on Figure 7 It can be seen that when the modulus of water glass in the cementitious material increases, the initial setting time and final setting time of NSF are shortened accordingly.
[0083] 3. Shrinkage performance test
[0084] After the cement mortar specimens are made, they are cured and demoulded, then installed in a vertical mortar shrinkage meter and moved into a test room with a temperature of 20°C and a relative humidity of 60% for 4 hours. The origin of the shrinkage meter is then adjusted with a standard rod, and the initial length of the specimen is recorded. The length of the specimen is then measured separately for each specimen, which is the length after drying.
[0085] The results of the shrinkage (drying shrinkage) of NFS cement mortar specimens are shown in Table 5.
[0086] Table 5 Drying shrinkage results of NFS cement mortar specimens
[0087] serial number <![CDATA[Shrinkage amount / 10 -6 > Example 1 1213 Example 2 1357 Example 3 1386 Example 4 1435 Example 5 1538 Example 6 1553 Example 7 1468 Example 8 1655 Example 9 1736
[0088] The results of the influence of the content of each component of slag-fly ash on the shrinkage of NSF cement mortar are shown in Figure 8 ,Depend on Figure 8It can be seen that when the proportion of fly ash in the cementitious material increases, the shrinkage deformation of NSF will decrease.
[0089] The effect of water glass modulus on the shrinkage of NSF cement mortar is shown in Fig. 9 ,Depend on Fig. 9 It can be seen that the shrinkage deformation of NSF first decreases and then increases with the increase of water glass modulus. The increase of water glass modulus in the range of 0.6 to 1.2 will increase the number of capillaries inside the structure, which gives more opportunities and paths for water to move, providing the system with a large amount of water to reduce self-shrinkage.
[0090] Because the mechanical properties of NSF cement mortar in Example 1, Example 4, and Example 7 all meet the requirements for base use, and the biggest disadvantage of alkali-activated slag-fly ash cementitious material is its fast setting time and large shrinkage, after comprehensive comparison, Example 1 is preferred as the mix ratio of base cementitious material for subsequent tests.
[0091] 4. Hydration products and their structural analysis
[0092] (1) Scanning electron microscopy (SEM)
[0093] The SEM image of NFS cement mortar (sample of Example 1) at 14 days is shown in Fig.10 The SEM image of NFS cement mortar (specimen I) at 28 days is shown in Fig.11 It can be seen that with the increase of sample curing time, in the alkaline environment provided by water glass, the dissolution amount of Al and Si ions in the silica-alumina raw material increases, and then more aluminosilicate gel is generated through migration, polycondensation and dehydration hardening process. At this time, relatively rich hydration products have been generated in the system, mainly in the form of lamellar CSH gel and CASH gel. The interweaving and overlapping of gel products can more effectively fill the pores in the matrix, reduce the porosity of the matrix, and ensure the formation of a more compact gel structure, thereby improving the mechanical properties of the material.
[0094] (2) X-ray diffraction (XRD)
[0095] The XRD patterns of NFS cement mortar (sample of Example 1) at 3d, 14d and 28d are shown in Fig.12 It can be seen that when the specimen is 3d old, there is a diffraction peak with a higher peak and a lower diffraction peak in the range of 20° to 30° in the spectrum, indicating that there are diffraction peaks in the amorphous structure, mainly CSH gel and a small amount of C(N)-ASH gel. In the early stage, the slag is mainly hydrated to release Ca + 、SiO4 4- 、A1O4 5-Hydrated CSH gel is generated, forming the source of early strength of the system. When the specimen is 14 days old, there are two diffraction peaks in the range of 20° to 30° in the spectrum. Compared with the diffraction peak at 3 days, the peak value becomes higher, indicating that hydration is still in progress and the system generates more CSH gel and C(N)-ASH gel. This is because as the fly ash and Ca(OH)2 in the system undergo a volcanic ash reaction, a secondary hydration reaction occurs. At the same time, the silicon aluminum oxide content in the fly ash is high, and the SiO2 / Al2O3 in the system increases. A large amount of new amorphous gel C(N)-ASH gel is generated in the system, which further improves the strength of the system. When the specimen is 28 days old, there are two diffraction peaks in the range of 20° to 30° in the spectrum, which are CSH gel and C(N)-ASH gel, indicating that the hydration reaction is still in progress in the later system, but the intensity of the reaction is much weaker than in the early stage.
[0096] Application Example 1
[0097] Taking Example 1 as the optimal ratio (slag: fly ash = 5:5, alkali activator dosage of 15%, water glass modulus of 1.0), the road performance of cement-slag based polymer cementitious material (cement-NFS) stabilized crushed stone was studied by conducting indoor tests such as unconfined compressive strength, indirect tensile strength, compressive rebound modulus and drying shrinkage of the mixture.
[0098] The mass percentage of NSF materials in cement-NFS materials is 0%, 50%, 75%, and 100%. According to the Technical Specifications for Highway Pavement Base Construction (JTG / TF20-2015), the gradation design of semi-rigid base materials is required first, and a gradation curve is designed within the CB-1 gradation range recommended by the specification ( Fig.13 ), through the aggregate grading design, determine the dosage ratio of 0-4.75mm, 4.75-9.5mm, 9.5-19mm, 19-26.5mm, as shown in Table 6, and then preset the cement-NSF dosage to 4%, 5%, and the moisture content to 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%. And prepare the specimens according to the proportions in Table 7.
[0099] Table 6 Synthetic gradation screening results
[0100]
[0101] Table 7 Design of proportion of different NSF
[0102]
[0103] (1) Compaction test
[0104] The heavy compaction test method was selected for testing. The specific compaction test method parameters are shown in Table 8.
[0105] Table 8 Compaction test method parameters
[0106]
[0107] The maximum dry density and optimum water content of cement-NSF crushed stone mixture under different NSF dosages are shown in Fig.14 and Fig.15 (In the figure, the proportion of cement-NSF is 5%, which represents the mass proportion of cement-NSF in the cement-NSF gravel mixture, and the proportion of NSF on the horizontal axis refers to the mass percentage of NSF in cement-NSF). It can be seen that with the increase of the proportion of NSF in the cement-NSF material, the optimal moisture content of the mixture with a cementitious material content of 4% and 5% increases, and the growth rate shows a gradually increasing trend. In the 5% gelling agent group, the optimal moisture content increased by 1.53%, 6.50% and 11.66%, respectively. With the increase of the proportion of NSF in the cement-NSF material, the maximum dry density of the mixture gradually decreases. When the proportion of NSF is 100%, the decrease is the largest. The mixture with a cementitious component content of 4% and 5% decreases by 1.70% and 1.77%, respectively. This may be because the fineness of the NSF material is smaller than that of cement, and the specific surface area is larger, so it has a higher water absorption rate. In addition, when the amount of cementitious material in the mixture is high, the dry density of the mixture during mixing and compaction gradually decreases with the increase of water content. Among other things, this phenomenon occurs mainly due to the large amount of cementitious material. In this case, the gaps filled by the crushed stone are fully filled, resulting in a relative reduction in the crushed stone aggregate. At the same time, the water absorption capacity of the crushed stone aggregate is much lower than that of the cementitious material, which leads to an increase in the amount of water required during mixing and compaction. In addition, since the cementitious material has a lower density, using a larger amount of cementitious material to stabilize the crushed stone will result in a lower dry density.
[0108] (2) Unconfined compressive strength test
[0109] According to the "Test Code for Inorganic Binder Stabilized Materials for Highway Engineering" (JTGE51-2009), unconfined compressive strength test was carried out.
[0110] The unconfined compressive strength test results are shown in Table 9. The relationship between the unconfined compressive strength of cement-NSF crushed stone mixture and the amount of NSF cementitious material is shown in Figure 16-17 , Fig.16 is the unconfined compressive strength of cement-NSF crushed stone mixture at different NSF dosages when the mass proportion of cement-NSF in the cement-NSF crushed stone mixture is 4%, Fig.17It is the unconfined compressive strength of cement-NSF gravel mixture at different NSF dosages when the mass proportion of cement-NSF in the cement-NSF gravel mixture is 5%.
[0111] Table 9 Unconfined compressive strength test results
[0112]
[0113] Note: The mixture with 4% cementitious content is recorded as H4, the mixture with 5% cementitious content is recorded as H5, and the mixture proportions are recorded as Ⅰ~Ⅷ respectively.
[0114] From Table 9 and Figure 16-17 It can be seen that the unconfined compressive strength of H4 and H5 specimens increases with the increase of curing age. The main strength of the mixture is generated within 7 to 28 days, and the growth rate slows down during 28 to 90 days. Among them, the strength growth rate of Group IV and VIII specimens from 7 to 28 days is the fastest, increasing by 30.61% and 29.53% respectively. In cement-NSF, the greater the proportion of NSF, the faster the strength growth rate of the mixture. Taking the compressive strength of H4 as an example, the compressive strength increases of Group II, III, and VI from 7 to 28 days are 23.40%, 35.88% and 30.61% respectively, and the strength increase of Group I is only 21.60%.
[0115] according to Figure 16-17 It can be seen that the growth rate of the mixture slowed down during the period from 28 to 90 days. Taking H4 mixture as an example, the increase in compressive strength of the specimens in groups I, II, III, and VI was 8.89%, 8.78%, 5.76%, and 7.85%, respectively. It can be seen that the increase was significantly lower than that from 7 days to 28 days, but the strength still increased, indicating that the hydration of the cementitious material in the system was still in progress. The hydration of slag in cement-NSF materials ensured the early strength, while the fly ash was less active and was mainly hydrated in the later period, ensuring the later mechanical properties of the mixture. At 90 days, the lowest strength of group I could still reach 6.13MPa, which could still meet the use requirements of first-class highways. As the proportion of NSF increased, the unconfined compressive strength of the mixture at all ages was higher than that of the control group. This was because of the advantages of alkali-activated cementitious materials. After the slag and fly ash were properly activated, higher mechanical properties would be generated in the early stage, mainly generating a large amount of CSH gel to enhance the bonding effect of the mixture. Therefore, under this system, the aggregates are interlocked and stabilized, and at the same time, the fine particles and the generated cementitious material are wrapped around each other and filled in the voids of the mixture, so that the strength of the mixture is further improved.
[0116] (3) Indirect tensile strength test
[0117] According to the provisions of the "Indirect Tensile Strength Test Method" (JTGE51-2009), the indirect tensile strength test results are shown in Table 10, and the relationship between the indirect tensile strength and the NSF content is shown in Table 10. Figure 18-19 , Fig.18 is the indirect tensile strength of cement-NSF crushed stone mixture under different NSF dosages when the mass proportion of cement-NSF in the cement-NSF crushed stone mixture is 4%, Fig.19 It is the indirect tensile strength of cement-NSF gravel mixture at different NSF dosages when the mass proportion of cement-NSF in the cement-NSF gravel mixture is 5%.
[0118] Table 10 Indirect tensile strength test results
[0119]
[0120] From Table 10 and Figure 18-19 It can be seen that the indirect tensile strength of H4 and H5 specimens increases with the increase of age. Group II has exceeded the indirect tensile strength of Group I at each age. The main strength of the mixture is generated within 7 to 28 days, and the growth rate slows down during 28 to 90 days. Among them, the strength growth rate of Group IV and Group VIII specimens from 7 to 28 days is the largest, increasing by 32.69% and 38.60% respectively. The strength increases of Group II, III, and IV specimens are 31.11%, 33.3%, and 32.69% respectively. During the period from 28d to 90d, the increase in indirect tensile strength of the mixture of H5 specimen was greater than that of H4 specimen. The increases of specimens in groups IV and VIII were 8.70% and 11.39%, respectively. The reason for this is that the strength of the mixture is linearly related to the amount of cementitious material added, which is beneficial to the strength growth. However, from an economic point of view, it is more economical to keep the amount of cementitious material as small as possible while meeting the requirements of the specifications. At the same time, if the amount of cementitious material added is too large, the shrinkage deformation caused by it will also become larger, which will have an adverse effect on the durability of the base layer.
[0121] Comprehensive analysis shows that the unconfined compressive strength and indirect tensile strength of the mixture have the same change pattern, both of which increase with the increase of the proportion of cementitious materials and NSF. The reason is that the unconfined compressive strength and indirect tensile strength are mainly affected by the bonding force between crushed stone aggregate and cementitious agent, and the strength is generated by the bonding of gel and the embedding of aggregate.
[0122] (4) Compressive rebound modulus test
[0123] The compressive resilience modulus test was carried out according to the "Testing Procedure for Inorganic Binder Stabilized Materials for Highway Engineering" (JTGE51-2009). The compressive resilience modulus results are shown in Table 11. The compressive resilience modulus changes with the NSF content. Figure 20-21 , Fig. 20is the compressive rebound modulus of cement-NSF crushed stone mixture under different NSF dosages when the mass proportion of cement-NSF in the cement-NSF crushed stone mixture is 4%, Fig.21 It is the compressive rebound modulus of cement-NSF gravel mixture at different NSF dosages when the mass proportion of cement-NSF in the cement-NSF gravel mixture is 5%.
[0124] Table 11 Compressive rebound modulus results
[0125]
[0126] It can be seen that the compressive resilience modulus values of H4 and H5 gradually increase with the increase of age. Taking H4 as an example, the compressive resilience modulus values of group II, III, and IV specimens at the age of 90d are 1.11 times, 1.30 times, and 1.18 times the values at the age of 28d. It can be seen that the greater the amount of NSF cementitious material, the higher the increase in the later compressive resilience modulus, which is the same as the change law of its compressive strength and indirect tensile strength. The compressive resilience modulus of group II to IV specimens is higher than that of group I specimens, and the compressive resilience modulus of group VI to VIII specimens is higher than that of group V specimens. The reason for this is that the size of the compressive resilience modulus is closely related to the compressive strength. The intercalation between the hydrated gel and the gravel is the decisive factor. The more hydrated gel, the tighter the gravel is combined, and the more it can resist external pressure, causing smaller deformation of the base layer and increasing the durability of the base layer.
[0127] (5) Shrinkage test
[0128] A standard beam specimen of 100mm×100mm×400mm was prepared for shrinkage test.
[0129] The relationship curves of the cumulative water loss rate, shrinkage strain, cumulative shrinkage strain and shrinkage coefficient of the mixture with different NSF cementitious material dosages are shown in Figure 22-25 . It can be seen that the water loss rate of the specimens in groups Ⅰ to Ⅳ increases with time, and the cumulative water loss rate increases significantly in the first 15 days; the water loss rate of the specimens decreases during the period of 15-30 days, and the cumulative water loss rate slows down; after 30 days, the cumulative water loss rate tends to be stable and the curve becomes flat. The total water loss rates of groups Ⅱ, Ⅲ, and Ⅳ are 5.85%, 6.65%, and 6.70%, respectively, and group Ⅰ is 4.00%, which indicates that the greater the proportion of NSF, the higher the total water loss rate of the mixture. With the increase of time, the shrinkage strain of the specimens tends to decrease gradually. The shrinkage strain decreases faster in the first 15 days and gradually slows down after 15 days. Compared with the control group, the greater the proportion of NSF, the greater the shrinkage strain of the specimens, indicating that the addition of NSF materials has a certain adverse effect on the shrinkage strain of the mixture, and the greater the amount of NSF, the more significant the adverse effect.
[0130] As time goes by, the shrinkage coefficient of the mixture gradually increases, with a faster growth rate in the early stage, but a slowdown in the later stage. It can be clearly seen from the figure that the shrinkage coefficient of the mixture in the control group is the largest, and the shrinkage coefficient of the mixture is significantly reduced after adding NSF cementitious materials.
[0131] (6) Microscopic analysis
[0132] The SEM images of cement-NSF crushed stone mixture of group II at 7d and 28d are shown in Figure 26-27 It can be seen that with the extension of age, more hydration products are generated, various hydration products gradually fill the gaps, the overall structure is becoming more and more dense, and the strength is also constantly increasing. The friction and embedding force between natural aggregates form the material's own strength. After the mixture is mixed and compacted, the pores of the natural aggregates gradually decrease, and the fine natural aggregates are filled between the large aggregates to form the initial strength. Due to the friction between them and the self-action force between the particles, the internal structure becomes more and more dense, forming a skeleton structure with higher strength. On the other hand, the cement hydration coagulation and hardening effect, as well as the cohesion and cementation effect generated by the hydration reaction of cement-NSF. After the mixture is mixed with water, cement-NSF reacts with water to generate CSH, CASH and NASH. As the hydration reaction proceeds, hydration products are continuously generated and intertwined with each other, making the mixture gradually firm. In addition, the hydration products also continuously fill the pores between the aggregates until they are completely hardened, and together with the aggregates, they form a structure with a certain strength density, thereby improving the mechanical strength of the cement-NSF crushed stone mixture.
[0133] Application Example 2
[0134] The road performance of cement-slag based polymer binder (cement-NFS) stabilized soil was studied, the mix ratios of the three variables, slag based polymer binder (NFS), cement and soil were designed, and experiments were carried out according to the mix ratios in Table 12 (wherein groups No. 1-4 are experimental groups, denoted as NSF-1, NSF-2, NSF-3 and NSF-4, and groups No. 5-8 are control groups, denoted as SN-N1, SN-N2, SN-N3 and SN-N4).
[0135] Table 12 Mix design (mass percentage)
[0136] serial number NSF% cement% earth% 1 6 - 94 2 8 - 92 3 10 - 90 4 12 - 88 5 - 6 94 6 - 8 92 7 - 10 90 8 - 12 88
[0137] (1) Compaction test
[0138] The results of the compaction test conducted according to the method in "T0843-2009" show that the 7d unconfined compressive strength of NSF-1~NSF-4 is between 2.25MPa and 4.75MPa, and the 7d unconfined compressive strength of SN-N1~SN-N4 is between 2.03MPa and 4.02MPa. The greater the dosage, the greater the strength. Analysis shows that the greater the dosage, the faster the reaction and the more products. On the one hand, the products will connect the loose soil particles more tightly, and on the other hand, the products can fill the soil pores and improve its structure, thereby increasing the compressive strength of the stabilized soil. The strength of NSF-1, NSF-2, and NSF-3 is 50.8%, 68.6%, and 94.1% of the strength of NSF-4. It shows that the strength increases rapidly when the NSF dosage increases from 6% to 10%; the strength of SN-N1, SN-N2, and SN-N3 is 50.5%, 62.6%, and 89.1% of the strength of SN-N4. Among them, the increase rate of NSF-1 to NSF-4 is faster, and its 7d unconfined compressive strength is 9.52% to 11.54% higher than that of SN-N1 to SN-N4. The 7d unconfined compressive strength of NSF-3 and SN-N3 reached 4.10MPa and 3.68MPa respectively, both of which meet the strength requirements of the specifications for the base of expressways and first-class highways, that is, the economic dosage of soil stabilizer is 10%.
[0139] (2) Water stability test
[0140] The water stability test scheme is shown in Table 13.
[0141] Table 13 Water stability test plan
[0142]
[0143] The oxidation age-unconfined compressive strength results are shown in Table 14.
[0144] Table 14 Oxidation age-unconfined compressive strength results
[0145]
[0146] It can be seen from Table 19 that with the increase of dosage and curing age, the compressive strength of the two stabilized soils is increasing. NSF stabilized clay reacts quickly in the early stage, and its strength tends to be stable after a period of curing. Therefore, it is necessary to pay attention to the early maintenance work during construction, which is conducive to the construction quality and the growth of roadbed strength. When the curing age is from 7d to 28d, the two stabilized clays increase rapidly. The 7d, 14d, and 28d strengths of NSF-1 to NSF-4 are higher than those of SN-N1 to SN-N4. The reason is that the hydration reaction of NSF stabilized clay generates gel substances such as CSH, CASH, and NASH. CASH has a strong bonding force; a turning point appears at 28d, and its unconfined compressive strength increases slowly in the later stage. The reason is that with the increase of curing age, the water content in the system increases, the concentration of alkali metal ions decreases, and the hydration rate slows down, resulting in a slow increase in the later strength; secondly, the newly generated gelling substances are easily wrapped on the surface of soil particles to hinder the hydration rate. This leads to a slow hydration reaction of the system. When the curing age is from 28d to 90d, the strength of NSF stabilized clay is still higher than that of cement. This is because the pozzolanic reaction of fly ash in the NSF system ensures the later strength.
[0147] The unconfined compressive strength (R1) of the specimens after immersion in water is shown in Table 15.
[0148] Table 15 Immersion curing-unconfined compressive strength
[0149]
[0150] It can be seen from Table 15 that under the condition of water-immersion curing, the dosage of curing agent has a great influence on the strength of stabilized soil. As the dosage increases, the strength also increases accordingly. In addition, extending the curing age will also increase the strength (between 28 days and 90 days, the strength changes slightly, but there is also an increase).
[0151] The water stability coefficients are shown in Table 16.
[0152] Table 16 Water stability coefficient
[0153] serial number 7d(%) 14d(%) 28d(%) 90d(%) NSF-1 79.1 83.4 73.7 86.8 NSF-2 83.7 86.4 87.9 86.5 NSF-3 84.3 88.4 86.2 88.2 NSF-4 88.6 85.7 91.7 91.0 SN-1 76.2 81.9 72.2 84.3 SN-2 80.8 81.5 77.1 82.5 SN-3 74.4 85.7 85.7 86.9 SN-4 83.3 82.2 88.2 88.6
[0154] It can be seen from Table 16 that, under the same age and the same dosage, NSF has better stability to soil than cement, which is manifested by a higher water stability coefficient. Under water-soaked curing conditions, with the increase of curing age, the water stability coefficients of the two stabilized clays show a trend of first decreasing and then increasing. Taking NSF-3 as an example, its water stability coefficient is between 84.3% and 88.2%, and the water stability coefficients after curing for 7 days and 90 days are 84.3% and 88.2% respectively, and the water stability coefficients after curing for 14 days and 28 days are 88.4% and 86.2% respectively.
[0155] Combined with the above performance test results, it can be seen that the slag-based polymer cementitious material proposed in the present invention uses slag and fly ash industrial solid waste as raw materials. The interweaving and overlapping of gel products can more effectively fill the pores in the matrix, reduce the porosity of the matrix, and form a more compact cementitious structure, thereby improving the mechanical properties of the material. The micro-aggregate effect, ball effect, and volcanic ash effect of fly ash all play a role in increasing the strength of the system. When cement-NSF is used to stabilize gravel, as the proportion of NSF increases, the unconfined compressive strength, indirect tensile strength, and compressive rebound modulus all increase to varying degrees. The 7d unconfined compressive strength and road performance of the 4% cement-NSF cementitious material stabilized gravel mixture can meet the requirements of the pavement base of different highway grades, which is an outstanding technical progress compared to the existing technology.
[0156] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A slag-based polymer cementitious material, characterized in that: Slag and fly ash are used as precursors, and water glass is used as an alkali activator, wherein the mass ratio of the slag to the fly ash is (5-7): (3-5), the amount of the water glass in the precursor is 15-25wt%, and the modulus of the water glass is 1.0-1.
4.
2. The slag-based polymer cementitious material according to claim 1, characterized in that: The mass ratio of the slag to the fly ash is 5:5, the content of the water glass in the precursor is 15wt%, and the modulus of the water glass is 1.
0.
3. The slag-based polymer cementitious material according to claim 1, characterized in that: The raw materials of the slag-based polymer cementitious material also include standard sand, naphthalene-based water reducing agent and water.
4. The slag-based polymer cementitious material according to claim 3, characterized in that: The water-to-cement ratio of the slag-based polymer cementitious material is 0.
4.
5. A method for preparing the slag-based polymer cementitious material according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: mixing water glass with water, adding slag, fly ash, standard sand and naphthalene series water reducing agent, mixing and stirring to obtain the slag-based polymer gelling material.
6. Use of the slag-based polymer cementitious material according to any one of claims 1 to 4 in pavement construction materials.
7. The use of the slag-based polymer cementitious material in pavement construction materials according to claim 6, characterized in that: The slag-based polymer cementitious material is used for stabilizing crushed stones in the road base, and the addition amount of the slag-based polymer cementitious material is 4%-5%.
8. The use of the slag-based polymer cementitious material in pavement construction materials according to claim 6, characterized in that: The slag-based polymer cementitious material is used for stabilized soil or concrete of a road base, and the addition amount of the slag-based polymer cementitious material is 6-12%.
9. The use of the slag-based polymer cementitious material in pavement construction materials according to claim 8, characterized in that: The addition amount of the slag-based polymer gelling material is 10%.
Citation Information
Cited By
Performance testing method and system for industrial solid waste green cementing material solidified loess foundation
CN120084980A
Composite soil stabilizer for water-rich low-temperature condition
CN121362020A
